Dynamic policies of admission to a two-class system based on customer offers - Örmeci, EL; Burnetas, AN; Emmons, H. (IIE Transactions (Institute of Industrial Engineers), 2002)
We consider the problem of dynamic admission control in a Markovian loss queueing system with two classes of jobs with different service rates and random revenues. We establish the existence of an optimal monotone policy. We also show that under certain conditions there exist preferred jobs from either class.
Keywords: Computer integrated manufacturing; Dynamic admission control; Markov processes; Markovian loss queueing system; Mathematical models; Optimization; Poisson distribution; Queueing networks; Scheduling; Servers; Theorem proving